A decoding scheme for the 4-ary lexicodes with D=3 - D. G. Kim; H. K. Kim (International Journal of Mathematics and Mathematical Sciences)
We introduce the algorithms for basis and decoding of quaternary lexicographic codes with minimum distance d=3 for an arbitrary length n.